A review of fire projects in Indonesia (1982-1998) - Dennis, R.A. (Center for International Forestry Research, 1999)
Fire in the wet tropical climate of Indonesia is not a new phenomenon. The 'Great Fire of Borneo' in 1982-83 was one of the worst fire events in recent decades. Small holders clearing land for cultivation were primarily blamed for starting fires that rapidly spread out of control. Subsequent fires linked to El Nino-Southern Oscilation occurred in 1987, 1991 1994 and most recently in 1997-98. The impact of the latest fire event is immense; estimates of the area burnt in 1997 vary between two and five million hectares (forest and non-forest), the number of people affected by smoke haze and fire at 75 million and the total economic costs in the region at as much as US$4.5 billion. The 1982-83 fires brought the issue to world attention. After 1992 three long-term projects were initiated with the objectives of management and monitoring of fires. These were the EU-Forest Fire Prevention and Control Project in Southern Sumatra (1995-1998), GTZ's Integrated Forest Fire Management Project in East Kalimantan (1994-2000), and JICA's Forest Fire Prevention and Management Project in Bogor, Jambi and West Kalimantan (1996-2001). In addition, the Indonesia-UK Tropical Forest Management Programme started in 1992 and comprised a number of components related to fires as part of its overall improved forest management objective. After the 1997 fires numerous short- and long-term fire projects were proposed and started. Others, such as the first phase of the WWF project and the ADB's regional (RETA) and national (ADTA) projects, within a short time frame try to cover many aspects of fire problem such as socio-economic assessments, fire-fighting, area estimates, economic and policy assessments and ecological assessments. Representing a longer-term approach, CIFOR-ICRAF-UNESCO propose an in-depth study of the underlying causes and effects of fires. In addition to the international response Indonesia has several government agencies charged with the task of preventing, monitoring and controlling land and forest fires. Following the forest and land fires of 1994, the National Coordination Team for Land and Forest Fire Control was established in 1995. Interest in fire is only short-lived after a major fire event. Before the 1994 fires little attention was paid to the fire problem and missions mainly focussed on control and prevention of fires. Most of the new generation of fire projects established in 1997-98 address both issues.